Effective supervision from research students' perspective. - Izah, Mohd Tahir; Engku Suhaimi, Engku Atek; Norizan, Abdul Ghani; Zulkifli, A. Manaf
There are many factors that determine the success of research students in doing their postgraduate programs. Of these are the supervisors and effective supervision. The aim of this paper is to identify the attributes of supervisors and examine elements of effective supervision from the graduate research students‟ perspective. In addition, the study also examines whether the means of the students‟ opinions on their supervisors and effective supervision differ by demographic factors (program, faculty, course structure, gender and semester). Descriptive statistics will be used to describe the sample and Pearson chi-square test will be employed to test students‟ opinions on their supervisors and effective supervision and their relationships with demographic factors. Our results suggest that the three most important attributes of supervisors are: supervisors should be friendly, approachable and flexible; knowledgeable and resourceful; and encourage students to work and plan independently. In addition, the results indicate that effective supervision means that supervisors are able to establish good and professional relationships with students; give support and guidance; and provide continuous motivation and inspiration. Using Pearson chi-square test, the results suggest that there are no significant differences in means between attributes of supervisors and effective supervision based on program, faculty, course structure, gender and semester.